2018
DOI: 10.1111/1744-7917.12582
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide toxicity associated with detoxification enzymes and genes related to transcription of cuticular melanization among color morphs of Asian citrus psyllid

Abstract: The Asian citrus psyllid (Diaphorina citri Kuwayama) is known to exhibit abdominal color polymorphisms. In the current study, susceptibility to four insecticides was compared among orange/yellow, blue/green and gray/brown color morphs of field collected D. citri. The LD values and 95% fiducial limits were quantified for each insecticide and color morph combination and ranged between 0.10 ng/μL (0.06-0.10) and 6.16 ng/μL (3.30-12.50). Second, we measured the detoxification enzyme activity levels of orange/yello… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 50 publications
0
22
1
Order By: Relevance
“…Similar to CYP6CY3 , CYP4 is another key detoxification CYP family in insects ( Silva et al, 2012 ). In an insecticide-resistant morph of the Asian citrus psyllid Diaphorina citri Kuwayama, the gene expressions of CYP4 family members were significantly higher than those in the susceptible morph ( Chen et al, 2018 ). In addition to the CytP450-dependent detoxification system, we also found that feeding on β-ocimene-treated plants induced the expression of GST in aphids, which has been identified as being involved in the adaptation to plant defensive metabolites in various insect species, including M. persicae ( Francis et al, 2005 ).…”
Section: Discussionmentioning
confidence: 93%
“…Similar to CYP6CY3 , CYP4 is another key detoxification CYP family in insects ( Silva et al, 2012 ). In an insecticide-resistant morph of the Asian citrus psyllid Diaphorina citri Kuwayama, the gene expressions of CYP4 family members were significantly higher than those in the susceptible morph ( Chen et al, 2018 ). In addition to the CytP450-dependent detoxification system, we also found that feeding on β-ocimene-treated plants induced the expression of GST in aphids, which has been identified as being involved in the adaptation to plant defensive metabolites in various insect species, including M. persicae ( Francis et al, 2005 ).…”
Section: Discussionmentioning
confidence: 93%
“…Physiological plasticity in insects can increase survival in the face of diverse environmental challenges (Chown 2001). In ACP, color polyphenism among genetically similar individuals has been linked to physiological states that differ in important life traits such as reproductive capacity, reproductive behavior, dispersal, resistance to insecticides, cold resistance, immunity, and interactions with microbes (e.g., CLas) (Tiwari et al 2013;Martini et al 2014;Stockton et al 2017;Hosseinzadeh et al 2019;Ibanez et al 2019;Chen et al 2019;Hosseinzadeh et al 2021;Martini et al 2021). However, associations between color morphology and feeding behavior have not been explored for all three ACP color types (blue-green, grey-brown, and yellow-orange), and investigations thus far have been limited to a single population of ACP collected in Florida (Ebert and Rogers 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Even though the mechanisms behind color type shifts are not clear, ACP color morphs exhibit significant differences in reproductive potential (Ibanez et al 2019), reproductive behavior (Stockton et al 2017), dispersal capacity (Martini et al 2014), resistance to insecticides (Tiwari et al 2013;Chen et al 2019), cold resistance (Martini et al 2021), immunity (Hosseinzadeh et al 2021) and CLas acquisition and inoculation (Hosseinzadeh et al, 2019). Many of these metrics (e.g., reproduction, dispersal or immunity) are energetically demanding processes that may drive foraging and feeding behaviors required to obtain sufficient nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Cuticular thickening is not limited to the procuticle, and also occurs at the epicuticle layer (Balabanidou et al ., 2018). We found up‐regulation (>6×) of a Yellow gene, which is associated with pigmentation and waterproofing of the epicuticle (Chen et al ., 2019). Certain quinone metabolites are produced in the cuticle in the process of scleretization, which crosslink with CPs (Mun et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%